SOME SOLUTIONS TO THE RICCATI DIFFERENTIAL EQUATION - Kujumdžieva-Nikoloska, Marija; Mitevska, Jordanka (Matematichki Bilten, 2005)
In this paper we give some conditions for existence of quasi-periodic solutions with a linear quasi-period and a constant quasi-periodic coefficient to the Riccati differential equation and we find these solutions.